Study on the rock physical mechanical properties evaluation of tight oil reservoir in Chang 7 member, Longdong area, Ordos Basin, China - Wang, Ruifei; Tang, Ying (Frontiers in Earth Science, 2024)
The study aims to investigate the rock mechanical properties of the Chang 7 member tight oil reservoir in the Longdong region of the Ordos Basin, China, with the goal of enhancing the efficiency of oilfield development. Despite numerous contributions in the field of rock mechanics, challenges persist in reconciling experimental results with actual geological conditions and achieving comprehensive understanding of rock mechanical properties in tight oil reservoirs. To address this, a variety of experimental methods were employed to systematically assess the mechanical properties of the target reservoir. Rock density was measured using volumetric methods, tensile strength was evaluated through the Brazilian test, uniaxial and triaxial compression tests were conducted to assess rock mechanics properties, and dynamic elastic modulus and Poisson's ratio were obtained via sonic velocity measurements. Furthermore, differential strain analysis and imaging log analysis were employed to determine the magnitude and direction of geostress. The results revealed that fine-grained sandstone exhibited higher rock density and relatively higher tensile strength, while muddy siltstone exhibited comparatively lower values in these aspects. Analysis of the influence of confining pressure on rock mechanics properties demonstrated a strong positive correlation between compressive strength and Young's modulus with confining pressure, while Poisson's ratio exhibited more irregular variations. Additionally, a mathematical relationship between dynamic and static rock mechanical parameters was established. Lastly, based on the characteristics of geostress, reliable foundations for optimizing hydraulic fracturing and wellbore layout were provided. This study has enriched and complemented the investigation of rock mechanical properties in tight reservoirs, offering vital parameters and theoretical support for the development of tight oil reservoirs. This bears significant importance in enhancing petroleum extraction efficiency and optimizing engineering design.